Effect of Biofertilizer and Weeding on the Growth Characters and Seed Yield of Summer Mungbean (Journal of Environmental Science and Natural Resources, 2015)
An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh from February to June 2010 to study the effect of bio fertilizer and weeding on the growth characters and yield of summer mungbean (cv. Binamoog-7). Experimental treatments comprised of (a) five levels of biofertilizer: 0, 1, 2, 3, 4 kg ha-1 and (b) four levels of weeding: no weeding, one weeding, two weeding, and three weeding. The experiment was laid out in a randomized complete block design with three replications. The results indicate that the highest plant height (58.83cm) was obtained at 60DAS from 4 kg biofertilizer ha-1 and the highest dry weight plant-1 (17.78g) at 60DAS was produced from 2 kg biofertilizer ha-1.Three times weeding produced highest plant height (41.69cm) and dry weight plant-1 (18.09g) at 60DAS and seed yield (1.96 t ha-1) was attained significantly at maximum level from the application of 2 kg ha-1biofertilizer. Application of 2 kg biofertilizer ha-1 with three times weeding was proved to be the best possible combinationDOI: http://dx.doi.org/10.3329/jesnr.v7i1.22150 J. Environ. Sci. & Natural Resources, 7(1): 87-92 2014